2011
DOI: 10.1002/pro.625
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the conformational changes of an intrinsically disordered peptide using a quartz crystal microbalance

Abstract: Intrinsically disordered peptides (IDPs) have recently garnered much interest because of their role in biological processes such as molecular recognition and their ability to undergo stimulus-responsive conformational changes. The block V repeat-in-toxin motif of the Bordetella pertussis adenylate cyclase is an example of an IDP that undergoes a transition from a disordered state to an ordered beta roll conformation in the presence of calcium ions. In solution, a C-terminal capping domain is necessary for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…The folding of the RTX domains could then be monitored by the change in the resonance frequency of the peptides as the β-roll formation affected the local mass and viscosity near the crystal surface. It was found that the quartz crystal could also serve as a capping group, stabilizing the C-terminus of the peptide and allowing for calcium-dependent folding ( Figure 2 A) [ 71 ]. Interestingly, some calcium-dependent changes were also seen when the peptides were immobilized by the N-terminus (and the C-terminus was uncapped) and it was assumed this was due to a molecular crowding effect on the surface.…”
Section: Block V Rtx Domain Of Adenylate Cyclase From Bomentioning
confidence: 99%
See 1 more Smart Citation
“…The folding of the RTX domains could then be monitored by the change in the resonance frequency of the peptides as the β-roll formation affected the local mass and viscosity near the crystal surface. It was found that the quartz crystal could also serve as a capping group, stabilizing the C-terminus of the peptide and allowing for calcium-dependent folding ( Figure 2 A) [ 71 ]. Interestingly, some calcium-dependent changes were also seen when the peptides were immobilized by the N-terminus (and the C-terminus was uncapped) and it was assumed this was due to a molecular crowding effect on the surface.…”
Section: Block V Rtx Domain Of Adenylate Cyclase From Bomentioning
confidence: 99%
“…Cyan fluorescence protein (CYP) and yellow fluorescence protein (YFP) were used to characterize the conformational change of the domain by FRET, and this led to the discovery that YFP could serve as a C-terminal capping group [ 70 ]. Tethering of the RTX domain to a QCM crystal allowed the surface to function as a terminal capping group [ 71 ]; ( B ) rearranged RTX domains were created to explore sequence modularity and functionality. Rearranged RTX repeats were built with or without the capping group [ 64 ]; and ( C ) different numbers of full-length RTX domains (each with C-terminal caps) were concatenated with linkers and used in biomolecular recognition and protein hydrogel studies [ 68 , 69 ].…”
Section: Figurementioning
confidence: 99%
“…To date there has been a limited number of reports 23,24 regarding IDP conformation studies using acoustic biosensors. Here we extend the discrete-molecule approach to the real time study of IDPs reversible expansion and collapse.…”
mentioning
confidence: 99%
“…[17][18][19][20] Evaluation on protein unfolding/folding energy is one of primary methods to understand protein conformational stability, 21 protein mutation effects, 22 and property changes of small compounds binding to protein. 23,24 Protein unfolding/folding commonly follows a canonical two-state mechanism, 25 where protein cooperatively transits from folded state (F or native state) to unfolded state (U or denatured state) during unfolding in a changing environment (or vise versa in protein (re)folding).…”
Section: Introductionmentioning
confidence: 99%